2012
DOI: 10.3733/ca.v066n02p55
|View full text |Cite
|
Sign up to set email alerts
|

No-tillage and high-residue practices reduce soil water evaporation

Abstract: Reducing tillage and maintaining crop residues on the soil surface could improve the water use efficiency of California crop production. In two field studies comparing no-tillage with standard tillage operations (following wheat silage harvest and before corn seeding), we estimated that 0.89 and 0.97 inches more water was retained in the no-tillage soil than in the tilled soil. In three field studies on residue coverage, we recorded that about 0.56, 0.58 and 0.42 inches more water was retained in residue-cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 10 publications
0
51
0
2
Order By: Relevance
“…Compared to other reports, this is still a comparatively low percentage (e.g. Unger et al 1991;Mitchell et al 2012).…”
Section: Mulchingmentioning
confidence: 52%
“…Compared to other reports, this is still a comparatively low percentage (e.g. Unger et al 1991;Mitchell et al 2012).…”
Section: Mulchingmentioning
confidence: 52%
“…4) by cooling the soil and reducing evaporation. Based on this, no-till was estimated to save 1/2 to 1 inch of water and residue retention was estimated to save 2 to 4 inches of water during the season (Mitchell et al 2012). Given the sensitivity of corn to drought stress, these significant savings could greatly improve corn's resiliency to reduced water supplies in California.…”
Section: Conservation Agriculturementioning
confidence: 99%
“…Nonetheless, recent work by Mitchell et al (2012) demonstrated how elements of conservation agriculture can benefit water-limited crops in California. Specifically, in trials conducted in the San Joaquin Valley, eliminating tillage prior to planting and retaining residues from the previous crop help to retain soil moisture ( fig.…”
Section: Conservation Agriculturementioning
confidence: 99%
“…Soil tillage affects soil water storage, crop water use, infiltration capacity of soils and soil water availability (Machado et al, 2008;Brunel et al, 2013). No tillage and reducing tillage increase water use efficiency (Casa and Cascio, 2008;Mitchell et al, 2012).…”
Section: Improving Crop and Land Managementmentioning
confidence: 99%